Self-determination theory in HCI: shaping a research agenda - Ballou,N; Deterding,S; Tyack,A; Mekler,ED; Calvo,RA; Peters,D; Villalobos,Zúñiga G; Türkay,S (ACM, 2022)
Self-determination theory (SDT) has become one of the most frequently used and well-validated theories used in HCI research, modelling the relation of basic psychological needs, intrinsic motivation, positive experience and wellbeing. This makes it a prime candidate for a ‘motor theme’ driving more integrated, systematic, theory-guided research. However, its use in HCI has remained superficial and disjointed across various application domains like games, health and wellbeing, or learning. This workshop therefore convenes researchers across HCI to co-create a research agenda on how SDT-informed HCI research can maximise its progress in the coming years.